Development of an optimized preoperative computed tomography imaging checklist for endoscopic sinus surgery utilizing a systematic review of the literature and the modified Delphi method. Issue 3 (4th August 2022) - Leong, Stephen; Yang, Nathan; Ray, Amrita; Akbar, Nadeem; Colley, Patrick M.; Signore, Anthony Del; Eloy, Jean Anderson; Govindaraj, Satish; Gudis, David A.; Helman, Samuel; Hsueh, Wayne; Iloreta, Alfred‐Marc; et al.
Abstract: Background: Critical review of computed tomography (CT) imaging is essential in preoperative planning for endoscopic sinus surgery. In this study, we used a systematic review and a modified Delphi method to develop a comprehensive checklist that facilitates preoperative review of sinus CT imaging. Methods: We performed a systematic review of PubMed, Embase, CINAHL, Cochrane, and Web of Science databases to identify existing checklists developed to evaluate sinus CT imaging. An inclusive list of items from these checklists was compiled and a modified Delphi methodology was used to assign ranked priority. The Delphi process involved 14 rhinologists and had three phases: an initial survey with Likert priority (scale of 1–9) and two rounds of live discussions followed by survey to confirm consensus. Results: Ninety‐seven possible checklist items were identified from a systematic review and panelist input. On initial survey, 63 items reached a consensus score of 7+, and 13 items had near consensus scores between 6 and 7; two of these 13 borderline items were retained after subsequent panelist discussion. The resulting items were consolidated into an 11‐item disease checklist and a 24‐item anatomical checklist; the anatomical checklist was further divided into six subsections: nasal cavity, maxillary, ethmoid, sphenoid, frontal, skull base, and orbit. Additionally, panelists identified six core aspects of patient history to consider prior to surgery. Conclusions: After establishing content validity through a systematic literature review and a modified Delphi method, we developed a comprehensive checklist for preoperative sinus CT imaging review; implementation and evaluation of validity among trainees will suggest overall utility.